Kemendesakan Pengaturan Pengawasan Eksternal Perilaku Hakim Konstitusi - Sukrisno; Marsudi Dedi Putra (Syntax Idea)
Judicial power is independent to administer justice to uphold law and justice. However, the exercise of his powers must not be left uncontrolled. In fact, modern supervision is needed to prevent abuse of power as has occurred. This article seeks new breakthroughs as necessary steps in carrying out external supervision of the behavior of Constitutional Justices. This type of research includes normative juridical with a statutory and conceptual approach. Meanwhile, the analysis used is analytical juridical and described qualitatively descriptively. Research results: (1) steps that can be taken to monitor the behavior of Constitutional Judges by making changes to the 1945 Constitution and/or forming laws; (2) the most appropriate construction of state institutions to supervise the behavior of Constitutional Judges is the Judicial Commission apart from the Financial Audit Agency and the Ombudsman Commission.